Evaluating Extended Field of View Imaging for Measuring Rectal Tumor Lowest Boundary to Anal Verge Distance via Transrectal Biplane Ultrasound - Zhang, Yan; Liang, Lu; Ma, Huachong; Han, Jiagang; Lv, Xiuzhang; Ge, Huiyu (Ultrasound International Open, 2025)
This study aimed to measure the precise distance from the lowest boundary of a rectal tumor to the anal verge (DTAV) in patients with rectal cancer. A retrospective analysis was performed on clinical data from 70 rectal cancer patients. DTAV measurements were collected using transrectal biplane ultrasound, MRI, and colonoscopy. The difference in DTAV measurements between the mean DTAV value obtained by ultrasound (USmean) and colonoscopy exhibited a difference of 0.22 cm. In contrast, the difference between USmean and MRI was 0.48 cm, while the difference between MRI and colonoscopy was −0.26 cm. The ICC for DTAV measurements demonstrated excellent agreement, with values of 0.948 between USmean and MRI, 0.942 between USmean and colonoscopy, and 0.943 between MRI and colonoscopy. The minimum DTAV value obtained by ultrasound (USmin) was 5.05 cm, the middle DTAV value obtained by ultrasound (USmid) was 5.10 cm, and the maximum DTAV value obtained by ultrasound (USmax) was 5.30 cm. Notably, the median values of the differences in DTAV measurements between USmax and USmin, USmax and USmid, as well as USmid and USmin, were 0.2 cm, 0.1 cm, and 0.1 cm, respectively. Furthermore, the consistency of DTAV measurements between USmin and USmid, USmax and USmid, as well as USmin and USmax was excellent, with all ICC values reaching 0.999. Additionally, the radiologistʼs reassessment of MRI DTAV data showed excellent consistency with the original results, with an ICC value of 0.985. Transrectal biplane ultrasound utilizing EFOV imaging technology exhibited both accuracy and reproducibility for measuring DTAV. This approach provided a highly efficient and practical clinical tool for DTAV measurement.
Keywords: rectal cancer; colonoscopy; MR imaging; transrectal biplane ultrasound; extended field of view technology